A light-driven, highly selective dehydrogenation method for producing olefins from light alkanes based on SiO2 confined coating

CN122955482APending Publication Date: 2026-10-23FUZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611028010.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-10
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0004]本发明在克服现有轻质烷烃光催化脱氢制烯烃技术中催化剂稳定性差、烯烃选择性有待提高、氧化物半导体晶格氧易参与副反应从而导致催化剂结构失活和过度氧化等不足,提供一种基于无定型SiO2限域包覆的光驱动轻质烷烃高选择性脱氢制烯烃方法

Benefits of technology

[0021](1)在室温、常压及光照射条件下,本发明催化剂对乙烷、丙烷、丁烷等C2-C4低碳烷烃的脱氢反应中,能够实现100%的烯烃选择性,完全抑制了CO2等深度氧化副产物的生成。这一性能得益于无定形SiO2壳层对金属氧化物晶格氧的有效物理隔离,以及对表面酸碱环境的精细调控。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122955482A_ABST
    Figure CN122955482A_ABST
Patent Text Reader

Abstract

The application discloses a method for preparing light alkane into olefin by high selectivity dehydrogenation based on SiO2 limited coating. The catalyst takes metal oxide semiconductor as the core, coats amorphous SiO2 shell outside, and loads Pt clusters with an average particle size of about 1 nm on the SiO2 shell, and the metal oxide is selected from at least one of ZnO, In2O3, TiO2 and SrTiO3. The preparation method comprises metal oxide synthesis, hot water etching coating porous amorphous SiO2 and photo-deposition loading Pt clusters. When the catalyst is used for photocatalytic low-carbon alkane C2-C4 dehydrogenation reaction, the selectivity of the olefin reaches 100%, and the catalyst has excellent long-term stability. The amorphous SiO2 shell can effectively inhibit the participation of metal oxide lattice oxygen in the side reaction, stabilize the catalyst structure, and at the same time form a weak acid and weak base surface environment to promote the desorption of the olefin product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of photocatalytic low-carbon alkane value-added technology, specifically relating to a catalyst for photo-driven highly selective dehydrogenation of light alkanes to olefins, its preparation method, and photocatalytic method. Background Technology

[0002] Low-carbon olefins (ethylene, propylene, butene, etc.) are among the most important basic raw materials in the chemical industry, widely used in the production of polymers, oxygen-containing compounds, and various fine chemicals. Currently, low-carbon olefins are mainly obtained through high-temperature thermochemical processes such as naphtha steam cracking and fluidized catalytic cracking. However, these traditional processes are typically carried out at high temperatures of 500–700 °C, resulting in extremely high energy consumption and significant problems such as carbon dioxide emissions and catalyst deactivation due to carbon buildup. Therefore, developing green technology routes for the efficient dehydrogenation of low-carbon alkanes to olefins under mild conditions is of significant practical importance.

[0003] Metal oxide semiconductors (such as ZnO and TiO2) are widely studied catalyst systems in photocatalytic dehydrogenation reactions due to their suitable band structure and good photochemical stability. However, the photocorrosion of the metal oxide itself or the irreversible consumption of lattice oxygen gradually alters the catalyst surface structure, leading to the deactivation of active sites and making it difficult to meet the reaction stability requirements for practical applications. Furthermore, the surface of metal oxides usually contains highly active lattice oxygen species, which can easily further oxidize the generated olefins into byproducts such as CO2, resulting in unsatisfactory olefin selectivity. In addition, the surface defects of unmodified metal oxides are unevenly distributed, and direct photodeposition of noble metal precursors often yields metal particles with large and uneven particle sizes, resulting in low atom utilization efficiency. Summary of the Invention

[0004] This invention overcomes the shortcomings of existing photocatalytic dehydrogenation to olefins technology for light alkanes, such as poor catalyst stability, the need to improve olefin selectivity, and the easy participation of oxide semiconductor lattice oxygen in side reactions leading to catalyst deactivation and over-oxidation. It provides a light-driven, highly selective dehydrogenation to olefins method based on amorphous SiO2 confined coating.

[0005] To achieve the above objectives, the present invention adopts the following technical solution:

[0006] The preparation of a Pt / metal oxide@SiO2 core-shell photocatalyst and its application in the photocatalytic dehydrogenation of low-carbon alkanes to homocarbon olefins are disclosed. The catalyst has a core-shell structure, with a confined core consisting of a metal oxide semiconductor, an amorphous SiO2 shell surrounding the metal oxide semiconductor core, and Pt clusters supported on the amorphous SiO2 shell. The metal oxide can be selected from ZnO, In2O3, TiO2, and SrTiO3, serving as the semiconductor core. The amorphous SiO2 shell is a continuous, porous coating layer with a thickness that can be precisely controlled at the nanometer level, ranging from 1 to 5 nm. The Pt clusters have a significantly smaller particle size than Pt nanoparticles directly loaded without SiO2 coating and exhibit a highly uniform distribution on the shell surface. The average particle size of the Pt clusters is 1 nm, and the Pt loading accounts for 0.1 to 5 wt% of the total catalyst mass.

[0007] Furthermore, a method for preparing the above-mentioned photocatalyst is provided, comprising the following steps:

[0008] (1) Provide metal-oxide-semiconductor;

[0009] (2) The metal oxide semiconductor is dispersed in an alcohol-water mixed solvent, and tetraethyl orthosilicate (TEOS) is added in the presence of ammonia. After vigorous stirring, hot water etching is performed. After separation, washing and drying, metal oxide@SiO2 core-shell particles are obtained.

[0010] (3) Disperse the metal oxide@SiO2 core-shell particles in water, add methanol and chloroplatinic acid solution, perform photodeposition under an inert atmosphere by irradiation with a light source, centrifuge and dry to obtain the photocatalyst.

[0011] Further, the metal oxide semiconductor mentioned in step (1) is ZnO, and its preparation method includes: mixing a soluble zinc salt aqueous solution with an alkaline solution to carry out a precipitation reaction, separating the precipitate, drying it, and then calcining it in an air atmosphere at 200~400 ℃.

[0012] Further, in step (2), the alcohol-water mixed solvent is a mixture of ethanol and water, and the amount of tetraethyl orthosilicate added is 0.2~2 mL of tetraethyl orthosilicate per 500 mg of metal oxide semiconductor; after stirring the reaction, the reaction mixture is allowed to stand at room temperature for 8-24 hours, then heated at 80-120 °C for 1-4 hours, and then separated, washed and dried.

[0013] Furthermore, in step (3), the light source used for photodeposition is a 300 W xenon lamp with an illumination time of 10-60 minutes, and the temperature is controlled by 25 ℃ condensate water during the photodeposition process.

[0014] Furthermore, a method for light-driven dehydrogenation of low-carbon alkanes to produce olefins is provided, wherein the low-carbon alkanes are brought into contact with the above-mentioned photocatalyst under light irradiation to undergo a dehydrogenation reaction to obtain olefins of the same carbon; wherein the low-carbon alkanes are C2-C4 alkanes, and the olefin selectivity reaches 100% under simulated sunlight irradiation.

[0015] In this invention, the amorphous SiO2 shell plays three key roles:

[0016] Firstly, it physically isolates the lattice oxygen from the metal oxide core from migrating to the surface, effectively suppressing side reactions such as the deep oxidation of olefins involving lattice oxygen.

[0017] Secondly, it stabilizes the bulk phase and surface structure of the metal oxide core, significantly reducing photocorrosion and irreversible chemical changes during the reaction process;

[0018] Third, it constructs a weak acid and weak base surface chemical environment, which weakens the adsorption strength of olefin products on the catalyst surface and promotes their timely desorption, thereby increasing the olefin selectivity to 100%.

[0019] Meanwhile, the presence of the amorphous SiO2 shell also constrains the Pt precursor during photodeposition due to the chemical environment of the shell surface, which is conducive to the formation of highly dispersed Pt clusters with a particle size of about 1 nm. Compared with the large-particle nanoparticles formed by directly loading Pt onto bare metal oxides, this significantly improves the atomic utilization efficiency and catalytic activity of noble metals.

[0020] The significant advantages of this invention are:

[0021] (1) Under room temperature, normal pressure and light irradiation conditions, the catalyst of the present invention can achieve 100% olefin selectivity in the dehydrogenation reaction of C2-C4 low-carbon alkanes such as ethane, propane and butane, and completely suppress the generation of deep oxidation byproducts such as CO2. This performance is due to the effective physical isolation of the amorphous SiO2 shell from the lattice oxygen of the metal oxide, as well as the fine control of the surface acid-base environment.

[0022] (2) The amorphous SiO2 shell acts as a protective layer, which can significantly suppress the photocorrosion and structural degradation of the metal oxide core in the photocatalytic reaction, and the catalyst maintains a stable conversion rate and selectivity during long-term continuous operation. In contrast, the Pt / metal oxide catalyst without SiO2 coating shows obvious deactivation in a shorter reaction time.

[0023] (3) By performing photodeposition on an amorphous SiO2 shell, Pt clusters with an average particle size of about 1 nm and highly uniform dispersion can be obtained. Compared with Pt nanoparticles formed by directly loading on bare metal oxides, the utilization rate of Pt atoms is greatly improved, which is beneficial to reducing the cost of catalysts.

[0024] (4) The preparation method of the present invention has mild conditions (operation at room temperature and pressure) and simple steps. The thickness of the SiO2 shell can be precisely adjusted by controlling the amount of tetraethyl orthosilicate added. This method is not only applicable to ZnO, but can also be extended to various metal oxide semiconductors such as In2O3, TiO2, and SrTiO3, and has strong material versatility.

[0025] (5) The catalytic reaction can be carried out at room temperature, normal pressure and light irradiation. It does not require high temperature and high pressure, external oxidant or halogenated additive. The process is safe and environmentally friendly, and energy consumption is greatly reduced. It has potential industrial application prospects. Attached Figure Description

[0026] Figure 1 The XRD pattern of Pt / ZnO@0.5SiO2 prepared in Example 1.

[0027] Figure 2 AC-HAADF-STEM images of Pt / ZnO@0.5SiO2 prepared in Example 1, (a) low magnification, (b) high magnification.

[0028] Figure 3 TEM image (a) and AC-HAADF-STEM image (b) of Pt / ZnO prepared for Comparative Example 1.

[0029] Figure 4 NH3-TPD (a) and CO2-TPD (b) spectra of Pt / ZnO@0.5SiO2 and Pt / ZnO prepared for Example 1 and Comparative Example 1, respectively.

[0030] Figure 5 The graph shows a comparison of the performance of Pt / ZnO@0.5SiO2 and Pt / ZnO prepared in Example 1 and Comparative Example 1 in the light-driven dehydrogenation of propane to propylene.

[0031] Figure 6 The graph shows a comparison of the stability of Pt / ZnO@0.5SiO2 and Pt / ZnO prepared in Example 1 and Comparative Example 1 in the light-driven propane dehydrogenation to propylene.

[0032] Figure 7 The graph shows a comparison of the performance of 1% Pt / ZnO@0.5SiO2 prepared in Example 1 in the light-driven dehydrogenation of ethane and isobutane to produce ethylene and isobutene.

[0033] Figure 8 A comparison of the performance of core-shell catalysts encapsulated with other metal oxides (In2O3, TiO2, and SrTiO3) on light-driven propane dehydrogenation. Detailed Implementation

[0034] To make the above-mentioned features and advantages of the present invention more apparent and understandable, specific embodiments are described below in detail. Unless otherwise specified, the methods of the present invention are conventional methods in the art.

[0035] Example 1: Preparation of Pt / ZnO@0.5SiO2 photocatalyst

[0036] The preparation steps of a Pt / ZnO@0.5SiO2 core-shell photocatalyst are as follows:

[0037] (I) Preparation of ZnO

[0038] 10 mmol Zn(NO3)2·6H2O was dissolved in 50 mL of deionized water. Then, 50 mL of a 0.2 mol / L Na2CO3 aqueous solution was added dropwise under magnetic stirring, resulting in a white precipitate. After stirring for another hour, the precipitate was collected by centrifugation and washed three times with deionized water. The precipitate was dried at 80 °C overnight, and then calcined in a muffle furnace at 300 °C for 4 hours in air to obtain a white ZnO powder.

[0039] (II) Preparation of ZnO@0.5SiO2 core-shell particles

[0040] Take 500 mg of the ZnO powder prepared above, add 6 mL of deionized water and 40 mL of anhydrous ethanol, and sonicate for 30 minutes. Add 2 mL of ammonium hydroxide aqueous solution (28 wt%) under magnetic stirring, then slowly add 0.5 mL of tetraethyl orthosilicate (TEOS). After vigorous stirring for 1 hour, collect the product by centrifugation, and wash three times each with ethanol and deionized water. Redisperse the product in 50 mL of deionized water and let it stand at room temperature for 12 hours. Then transfer it to an oven and heat at 100 °C for 2 hours, centrifuge, wash three times with water, and dry in a vacuum oven at 60 °C to obtain ZnO@0.5SiO2 core-shell particles (denoted as ZnO@0.5SiO2).

[0041] (III) Preparation of 1%Pt / ZnO@0.5SiO2

[0042] Take 100 mg of the above ZnO@0.5SiO2 core-shell particles, add 10 mL of deionized water and 1 mL of methanol, and ultrasonically disperse for 5 minutes. Add 100 μL of chloroplatinic acid aqueous solution (H2PtCl6·6H2O, Pt concentration 10 mg / mL) while stirring. Seal the reaction flask, evacuate it, and purge it three times with high-purity Ar gas. Irradiate the reaction flask with a 300 W xenon lamp for 30 minutes, using a 25 ℃ circulating condenser for temperature control during irradiation. After irradiation, collect the product by centrifugation, wash it three times with deionized water, and dry it under vacuum at 60 ℃ to obtain a Pt / ZnO@0.5SiO2 photocatalyst with a Pt loading of 1 wt%.

[0043] Figure 1 The XRD patterns of the prepared ZnO, ZnO@0.5SiO2, and 1%Pt / ZnO@0.5SiO2 are shown. The characteristic diffraction peaks of the ZnO@0.5SiO2 catalyst are consistent with those of the ZnO standard card (PDF#36-1451), with only a slight decrease in peak intensity, indicating that amorphous SiO2 forms a uniform coating on ZnO. No characteristic diffraction peaks of Pt were observed in the 1%Pt / ZnO@0.5SiO2 sample, indicating that the Pt species are highly dispersed.

[0044] Figure 2 Aberration-corrected high-angle annular dark-field scanning transmission electron microscope (AC-HAADF-STEM) was used to perform the aberration correction on the prepared catalyst. Figure 2 Figure a shows that Pt species are uniformly distributed in clusters on the SiO2 shell, with an average particle size of about 1 nm. Figure 2 Image b clearly shows lattice fringe spacings of approximately 0.281, 0.247, and 0.260 nm, corresponding to the (100), (101), and (002) crystal planes of hexagonal ZnO, respectively. Simultaneously, iDPC technology confirms that the ZnO core surface is covered by a continuous and dense SiO2 shell with a thickness of approximately 1 nm.

[0045] Comparative Example 1: Preparation of Pt / ZnO (without SiO2 coating)

[0046] 100 mg of ZnO powder prepared in step (I) of Example 1 was taken directly and subjected to photodeposition of Pt under the conditions of step (III) of Example 1 without SiO2 coating to obtain a 1 wt% Pt / ZnO catalyst. Transmission electron microscopy showed that Pt was supported on the ZnO surface in the form of nanoparticles with a particle size of about 5-15 nm and uneven distribution.

[0047] Figure 3 Transmission electron microscopy (TEM) characterization of Pt in the middle showed that Pt existed in the form of nanoparticles and was unevenly distributed. Figure 3 The AC-HAADF-STEM image of b further reveals the interplanar spacing d = 0.23 nm, corresponding to the (111) crystal plane of the Pt nanoparticles.

[0048] Figure 4The figures show the NH3-TPD and CO2-TPD spectra of ZnO and 1% Pt / ZnO@0.5SiO2 prepared in Example 1, and Pt / ZnO prepared in Comparative Example 1. As shown, Pt loading has a weak effect on the acid-base sites of ZnO; while SiO2 coating (Pt / ZnO@SiO2) can directionally increase weak acid sites, significantly suppress strong acid sites, and shield medium-strong base and strong base sites, retaining only weak base sites. The SiO2 coating as a whole achieves passivation of strong acid and strong base centers, while providing abundant weak acid and weak base active sites, which is beneficial for the desorption of the product ethylene.

[0049] Example 2 Preparation of ZnO catalysts with different SiO2 coating amounts

[0050] The procedure was followed as in Example 1, except that in step (ii), the amount of tetraethyl orthosilicate added was 0.2 mL, 1 mL, and 2 mL, respectively, to obtain catalysts with different SiO2 shell thicknesses, denoted as ZnO@0.2SiO2, ZnO@1SiO2, and ZnO@2SiO2, respectively. The subsequent photodeposition of Pt was the same as in Example 1.

[0051] Example 3 Preparation of Pt / In2O3@SiO2

[0052] The procedure was followed as in Example 1, except that the metal oxide prepared in step (a) was In₂O₃. In₂O₃ can be obtained by precipitating an aqueous solution of In(NO₃)₃ with ammonia, drying the resulting precipitate, and then calcining it at 400°C for 3 hours in air. The subsequent SiO₂ coating and Pt photodeposition steps were the same as in Example 1.

[0053] Example 4 Performance Test of Propylene Dehydrogenation Driven by Light

[0054] Photocatalytic propane dehydrogenation was carried out in a fixed-bed reactor using a xenon lamp as a simulated light source.

[0055] The experimental procedure is as follows: 100 mg of the 1% Pt / ZnO@0.5SiO2 catalyst prepared in Example 1 and the 1% Pt / ZnO catalyst prepared in Comparative Example 1 were respectively mixed with quartz sand (50-80 mesh, analytical grade) and then loaded into a quartz reaction tube. First, argon gas was used to purge the reaction system to remove impurity gases (such as oxygen and carbon dioxide), and then the reaction was switched to the feed gas (5% C3H8 / Ar, space velocity 9000 mLg). -1 h -1 Samples were taken periodically during the reaction, and the products were analyzed online by gas chromatography equipped with a thermal conductivity detector and a flame ionization detector.

[0056] Figure 5A performance comparison of the 1% Pt / ZnO@0.5SiO2 catalyst prepared in Example 1 and the 1% Pt / ZnO catalyst prepared in Comparative Example 1 in light-driven propane dehydrogenation to propylene. As shown in the figure, the propylene yield of the Pt / ZnO catalyst is 3010 μmol·g. -1 ·h -1 However, the propylene selectivity was only 68.9%, and it was accompanied by CO2 generation; while the propylene yield of Pt / ZnO@0.5SiO2 was 2648 μmol·g. -1 ·h -1 The propylene selectivity reached 100%, and no CO2, CH4, or other byproducts were detected.

[0057] Figure 6 A comparison of the stability of the 1% Pt / ZnO@0.5SiO2 catalyst prepared in Example 1 and the 1% Pt / ZnO catalyst prepared in Comparative Example 1 in the photo-driven dehydrogenation of propane to propylene is presented. As shown in the figure, the activity of the Pt / ZnO catalyst decreased significantly after 4 h of reaction, and the selectivity also slightly decreased; while the Pt / ZnO@0.5SiO2 catalyst showed no significant decline in catalytic activity after 40 h of continuous reaction, and the propylene selectivity remained at 100%. This comparison fully demonstrates the decisive role of the amorphous SiO2 coating layer in improving olefin selectivity and catalyst stability.

[0058] Example 5 Performance Test of Light-Driven Ethane / Butane Dehydrogenation to Ethylene

[0059] Using the same conditions as in Example 4, the reaction gases were replaced with ethane and isobutane (5% C2H6 / Ar or 5% i-C4H). 10 / Ar, space velocity is 9000 mL g -1 h -1 ).

[0060] Figure 7 The performance of 1% Pt / ZnO@0.5SiO2 prepared in Example 1 in the light-driven dehydrogenation of ethane and isobutane to ethylene and isobutene is compared. As shown in the figure, the selectivity for both ethylene and isobutene reached 100%, demonstrating that this catalyst has good versatility for the dehydrogenation of low-carbon alkanes.

[0061] Example 6 Performance Testing of Other Metal Oxide@SiO2 Catalysts

[0062] Following the method in Example 1, the catalytic performance of other metal oxides (In2O3, TiO2, and SrTiO3) on the propane dehydrogenation reaction was tested. Figure 8 The results showed that the propylene selectivity of all three catalysts reached 100%, demonstrating the universality of this coating strategy.

[0063] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made within the scope of the claims of the present invention should be included in the scope of the present invention.

Claims

1. A catalyst for highly selective dehydrogenation of light alkanes to olefins based on SiO2 confined coating, characterized in that: The catalyst has a core-shell structure, with a confined core of a metal oxide semiconductor, an amorphous SiO2 shell surrounding the metal oxide semiconductor core, and Pt clusters supported on the amorphous SiO2 shell.

2. The catalyst according to claim 1, characterized in that: The metal oxide semiconductor is selected from at least one of ZnO, In2O3, TiO2, and SrTiO3.

3. The catalyst according to claim 1, characterized in that: The average particle size of the Pt clusters is 1 nm, and they are uniformly distributed on the amorphous SiO2 shell.

4. The catalyst according to claim 1, characterized in that: The Pt loading accounts for 0.1 to 5 wt% of the total catalyst mass.

5. The catalyst according to claim 1, characterized in that: The thickness of the amorphous SiO2 shell is 1~5 nm.

6. The method for preparing the catalyst according to any one of claims 1-5, characterized in that: Includes the following steps: (1) Provide metal-oxide-semiconductor; (2) The metal oxide semiconductor is dispersed in an alcohol-water mixed solvent, and tetraethyl orthosilicate is added in the presence of ammonia. After vigorous stirring, hot water etching is performed. After separation, washing and drying, metal oxide@SiO2 core-shell particles are obtained. (3) Disperse the metal oxide@SiO2 core-shell particles in water, add methanol and chloroplatinic acid solution, perform photodeposition under an inert atmosphere by irradiation with a light source, centrifuge and dry to obtain the catalyst.

7. The method according to claim 6, characterized in that, The metal oxide semiconductor mentioned in step (1) is ZnO, and its preparation method includes: mixing a soluble zinc salt aqueous solution with an alkaline solution to carry out a precipitation reaction, separating the precipitate, drying it, and then calcining it in an air atmosphere at 200~400 ℃.

8. The method according to claim 6, characterized in that, In step (2), the alcohol-water mixed solvent is a mixture of ethanol and water, and the amount of tetraethyl orthosilicate added is 0.2~2 mL of tetraethyl orthosilicate per 500 mg of metal oxide semiconductor; after stirring the reaction, the reaction mixture is allowed to stand at room temperature for 8-24 hours, then heated at 80-120 °C for 1-4 hours, and then separated, washed and dried.

9. The method according to claim 6, characterized in that, In step (3), the light source used for photodeposition is a 300W xenon lamp with an illumination time of 10-60 minutes, and the temperature is controlled by 25°C condensate water during the photodeposition process.

10. The application of the catalyst according to claim 1 in the photocatalytic dehydrogenation of low-carbon alkanes to olefins, characterized in that, include: Under light irradiation, low-carbon alkanes are brought into contact with a catalyst to undergo a dehydrogenation reaction to obtain olefins of the same carbon; and the low-carbon alkanes are C2-C4 alkanes, with olefin selectivity reaching 100% under simulated sunlight irradiation.